Systemic and local toxicity assay of an aqueous extract of Larrea divaricata Cav.: role of NDGA - Peralta, Ignacio Nahuel (2015)
Larrea divaricata Cav. (Zygophyllaceae) is an autochthonous plant of South America, widely distributed in Argentina. It is used in folk medicine as an anti-inflammatory drug. By other way, presents well documented antitumoral and immunomodulatory effects. Nordihydroguaiaretic acid (NDGA), an antioxidant compound, had been previously described in this plant. Nowadays a formulation for hair growth based on an extract of L divaricata is commercialized in Argentina. Taken these into account, the objective of this work was to determine the systemic and local toxicities of the aqueous extract of L divaricata, by giving it under oral and topical administration. Also, it was proposed to analyze the participation of NDGA in the systemic toxicity of the plant extract. The extract presented low acute toxicity, and the histopathological examination of the tissues did not show any signal of toxicity at the same time that did not affect biochemical parameters except eosinophils which were decreased by the treatment. Which is more; the extract did not exert dermatological or ocular irritation. It is important to note that in relation to its innocuousness and pharmacological properties other phytotherapy formulations could be prepared in a future.